I am the messenger - Zusak, Markus (New York Alfred A. Knopf Distributed by Random House, 2006)
After capturing a bank robber, nineteen-year-old cab driver Ed Kennedy begins receiving mysterious messages that direct him to addresses where people need help, and he begins getting over his lifelong feeling of worthlessness
"A Borzoi book"--T.p. verso
Originally published: The messenger. Australia : Pan Macmillan Australia, 2002
Michael L. Printz Award Honor Book, 2006
1
Keywords: Heroes -- Fiction; Self-esteem -- Fiction; Taxicab drivers -- Fiction